Globalna ekspansja przedsiębiorstw indyjskich - Gabryszak, Renata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
In the recent few years the Indian companies have increased significantly their foreign investement. Only in the first quarter of 2007 Indian firms have announced 34 foreign takeovers worth more than 10,7 billion dollars and in 2006 they invested abroad 23 billion dollars, more than five times the previous record and more than the investments made by foreigners in Indian companies. The most visible takeover in 2006 was the acquisition by the Indian company Mittal Steel the European steel giant Arcelor for 23 billion dollars. Other, biggest acquisitions include the purchase by Hindalco in February 2007 an American company Novelis for 6 billion dollars and the purchase of Anglo-Duch company Corus by Tata Steel, India, a biggest private steelproducer for 13,2 billion dollars. It is almost certain that Indian companies continue globalizing partly by buying foreign companies. Thus in the near future the tide of foreign acquisitions by Indian companies will continue to rise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 93-100